The Reconstruction of The Livelihood Concept from A Mubādalah Perspective in Lampung Province - Nur, Efa Rodiah; Mu’in, Fathul; Hamsidar, Hamsidar (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The laws and regulations in Indonesia exhibit gender bias, resulting in a rise in divorce cases within the Religious Courts. This can be attributed to the prevailing perception among women that the burden for sustaining livelihoods lies mostly with their husbands. This case pertains to the challenge of formulating legislation that effectively incorporates the notion of livelihood reconstruction while avoiding any gender biases. The objective of this study is to provide a re-evaluation of the notion of livelihood in order to facilitate the development of novel legal products that are more suited to meet contemporary demands. This is qualitative research, wherein data was collected from the Religious Courts in Lampung and subsequently examined through the use of the mubādalah theory. The present study has identified that the prevalence of divorce in Lampung may be attributed to the provisions outlined in Law no. 1 of 1974 and Compilation of Islamic Law (KHI). These legal provisions alone mandate husbands to provide financial support, hence leading to the increased occurrence of divorce. The implementation of these two legislation led to a notable rise of 34.25% in the occurrence of contested divorces within the Province of Lampung. This increase can be attributed to several grounds, including income-related issues accounting for 41.3%, disagreements and domestic violence contributing to 33.3%, and other miscellaneous variables comprising 28% of the overall increase. The promotion of family resilience entails the establishment of a symbiotic partnership between spouses, thereby reinforcing the husband-wife paradigm. This entails the implementation of rights and responsibilities, particularly in relation to income, to foster interdependence and mutual support within the marital union. The novelty of this study is in the ability of the idea of mubādalah to establish a connection between husbands and wives, enabling them to fulfil their respective rights and obligations, particularly in terms of partnership and mutual support within the context of cohabitation.